An overview of informed consent in dentistry in Malaysia/ Haniwarda Yaakob - Yaakob, Haniwarda (Faculty of Medicine, 2023)
Introduction: Obtaining informed consent from patients is a fundamental legal and ethicalelement that is required of dental practitioners. From routine procedures such as dental fillingor scaling to more complicated procedures such as oral surgeries, it is imperative that patients'informed consent be acquired. Failure to procure a valid consent from patients prior toembarking on any dental treatment may cause several potential legal repercussions againstdental practitioners. This paper, thus, seeks to discuss the issue of informed consent withparticular reference to dental practice. It begins with an explanation on the laws governinginformed consent in Malaysia. Then, an analysis on the ethical aspect behind the need toobtain patient's consent, namely patient autonomy is provided. This is followed with a discussion on the potential legal consequences for failure to obtain informed consent, limitingto civil actions only. Methods: This is a descriptive paper that adopts legal doctrinal andqualitative method of analysis. Conclusion: The precondition of obtaining patients' informedconsent is a fundamental aspect in dental practice both for patients and dental practitioners.